Ecologia das relações comunicacionais: de paredes... a pontes... - Nádia C. Lauriti (EccoS – Revista Científica)
This text aims to think about the processes involved with a communication pedagogics, considering the core role of emotion as modulator of cognitive processes.In this context, an effective communication model which operates with ecologic rationality should not exclude affectivity, the acceptance of differences, and mutual respect. This model establishes a modus comunicandi which rescues the sensitive logic, drives away the inflexibility of "walls" as paradigm blocks, concept mortar, and paralyzing definitions with which structures with no meaning are raised, in order to benefit with bridges which give way to new models of communicative pedagogic relations which give priority to how to learn to learn and what is the value of commitment, instead of what to teach and what is needed to compromise with.